Cross-cultural interaction in Indian English fiction - Chadha, Ramesh (National Book Organisation, 1988)
Study of Kamala Markandaya, b. 1924, and Ruth Prawer Jhabvala, b. 1927, Indian women novelists.
Bibliogr. u. Literaturverz. S. [147] - 163
Keywords: Jhabvala; Ruth Prawer <1927->; Markandaya; Kamala <1924->; Jhabvala; Ruth Prawer; Markandaya; Kamala; Geschichte; Indic fiction (English); Intercultural communication in literature; Women and literature; Roman